Pengaruh Sertifikat Halal Terhadap Penjualan dan Persepsi Konsumen Umkm Farah Cakes Di Rungkut Menanggal - Muhammad Syihabuddin Ridho; Afrizal Akbar Sanjaya (Randang Tana - Jurnal Pengabdian Masyarakat, 2024)
This article aims to evaluate the impact of halal certification on sales in Micro, Small, and Medium enterprises (MSMEs) pizza businesses, with a specific focus on consumer response. The study utilizes survey methods and data analysis to assess whether halal certification influences consumer purchase decisions. The implementation method consists of three stages: Socialization, Assistance, and Evaluation. The findings demonstrate that halal certification has a significant positive influence on MSMEs pizza sales, creating consumer trust, and enhancing preference for halal products. The implications of this research provide strategic guidance for MSMEs pizza businesses in addressing a market that is increasingly concerned about the halal aspects of products